1995
DOI: 10.1074/jbc.270.41.23975
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of Peroxisome Proliferator-activated Receptors by Eicosanoids

Abstract: Peroxisome proliferator-activated receptors (PPARs) are nuclear hormone receptors that regulate gene transcription in response to peroxisome proliferators and fatty acids. PPARs also play an important role in the regulation of adipocyte differentiation. It is unclear, however, what naturally occurring compounds activate each of the PPAR subtypes. To address this issue, a screening assay was established using heterologous fusions of the bacterial tetracycline repressor to several members of the peroxisome proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
408
3
6

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 642 publications
(442 citation statements)
references
References 58 publications
23
408
3
6
Order By: Relevance
“…This suggests that such HETE may be a mediator of the adipogenesis activation in our experimental model. This is in agreement with the fact that 8-HETE is a PPARa activator, and it can induce the 3T3-L1 pre-adipocyte differentiation toward adipocytes (Yu et al 1995). The studied HETE in cells induced to differentiate into osteoblasts were present at higher concentrations than in adipogenic media, in general.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This suggests that such HETE may be a mediator of the adipogenesis activation in our experimental model. This is in agreement with the fact that 8-HETE is a PPARa activator, and it can induce the 3T3-L1 pre-adipocyte differentiation toward adipocytes (Yu et al 1995). The studied HETE in cells induced to differentiate into osteoblasts were present at higher concentrations than in adipogenic media, in general.…”
Section: Discussionsupporting
confidence: 88%
“…LOX acts on liberated free AA to generate hydroperoxyeicosatetraenoic acids, which are unstable intermediates, being further either hydrolyzed into hydroxyeicosatetraenoic acids (HETE) via lipoxygenase catalysis or by non-enzymatic oxidative reactions (Niki et al 2005), or enzymatically converted into leukotrienes such as 5(6)-epoxy(oxido)eicosatetraenoic acid (leukotriene A4; LTA4) and lipoxins, which may be involved in important physiological events such as inflammation (Wahli and Michalik 2012). On the other hand, the HETE are PPARc agonists and may influence cellular differentiation (Ban et al 2011;Yu et al 1995). Additionally, LTA4 may be further converted into either dihydroxyeicosatetraenoic acid (LTB4) by an epoxide hydrolase or hydroxy-glutathionyleicosatetraenoic acid (LTC4) by a glutathione transferase (Needleman et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…PPARβ/δ agonists include linoleic acid, oleic acid, arachidonic acid and EPA, which has been co-crystallized within the ligand binding domain of this nuclear receptor [25]. Prostaglandin A1 (PGA1), PGD2 and PGD1 can activate PPARβ/δ in reporter assays [27]. Similar to PPARα and γ, incubation of triglyceride rich lipoproteins with LPL results in the production of PPARβ ligands [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Another molecular mechanism for the action of PUFA on cell death may be transmitted via PPAR receptors acting as transcription factors in combination with fatty acids. [42][43][44][45][46] Three human PPAR receptors (␣, ␦ and ␥) have been identified, and mRNA analyses demonstrated that all three receptors were expressed in U-698, Raji and Ramos cells (Finstad et al unpublished data). A possible mechanism whereby activation of PPAR receptors may induce apoptosis, may be via antagonizing the activity AP-1, NF-B and STAT, 47 as these transcription factors may influence the cellular suicide program.…”
Section: Discussionmentioning
confidence: 99%